Comparative study on the cervical range of motion in elderly individuals with different fitness levels - Carvalho, Cristiano Oliveira de; Magalhães, Denis Aron dos Santos; Silva Junior, José Alberto Alves; Bicalho, Luis Flávio Horta; Costa, Ana Paula Bitarães; Costa, Leonardo Oliveira Pena; Figueiredo, Vânia Ferreira de (Acta Fisiátrica, 2006)
The aim of this study was to analyze and compare the cervical range of motion (ROM) in elderly people with different fitness levels. Methods: Forty asymptomatic volunteers aged between 60-75 years old were recruited and classified based on their respective fitness level. The volunteers were then submitted to the measurement of cervical ROM with the Cervical Range of Motion (CROM) inclinometer by a blinded examiner. An intrarater reliability test was also performed to evaluate the examiner's reproducibility. Results: There were no significant differences regarding flexion and extension movements in both groups. The lateral right and left flexion and right and left rotation were statistically higher in the fitness group compared to the sedentary individuals. Conclusion: We concluded that the fitness level can be beneficial to preserve cervical ROM in elderly people.